Газета "Одесский вестник” (1827–1894) як історичне джерело з історії Одеського інституту шляхетних дівчат - Коробчук, А. (Чорноморська минувшина, 2020)
Метою статті є аналіз джерелознавчої інформації на шпальтах газети «Одесский вестник» для вивчення теми «Історія Одеського інституту шляхетних дівчат». Наукова новизна полягає в тому, що вперше було здійснено пошук за даною тематикою в одному з провідних місцевих видань. Отже, публікації в «Одесском вестнике» є допоміжним джерелом з історії Одеського інституту шляхетних дівчат. Статті в газеті «Одесский вестник» доповнюють наявні архівні та статистичні документи, що стосуються функціонування закладу освіти. Газета періодично висвітлювала новини та оголошення Інституту. У різний час вони знаходили своє місце в різних рубриках: «Внутрішні відомості», «Повідомлення», «Місцева хроніка», «Оголошення». The purpose of the article is to analyze source information in newspaper «Odessa Herald» to study the topic "History of the Odessa Institute of Noble Maiden". A phenomenon in the education system of the Russian Empire XVIII-XIX century there was the emergence of women's schools, institutes of noble maiden. Odessa Institute of Noble Maiden was a closed privileged educational establishment in the south of the Russian Empire, which belonged to the 1 st. level of the department of Empress Maria establishments. Beginning in 1827, the «Odessa Herald» was published twice a week in French (Journal d’Odessa) and Russian. It is important that the existence of the edition coincides with a significant period of operation of the Institute (65 years). The scientific novelty is that for the first time a search was conducted on the above topics in one of the leading local edition. The author carried out a frontal review of the "Odessa Herald" for 1829- 1890. On the pages of the newspaper were found 200 notes reflecting the history of the Institute. Publications were divided into two groups: 1. News, 2. Announcements. The research methods are based on the main principles of historicist tradition, scientific objective, comprehensive approach and data classification. In order to achieve the purpose, the author uses a number of general scientific methods (analytic, synthesis, classification) as well as specific historical methods, such as problematic and chronological, comparative and method of periodization. The newspaper «periodically covered the news and announcements of the Institute, which aimed to inform parents, relatives and the public about past ceremonial events, changes in functioning, as well as the urgent needs of the school. At different times, they found their prominent place in various sections: "Inside", "Messages", "Local Chronicle", "Announcements". The materials in the "Announcements" section are the most quantitative, but insignificant for the study of the history of the Institute. Periodic articles on the issue of boarding houses, which were quite extensive in scope, are important for reproducing the lists of students of the Institute, household, etc. moments related to the functioning of the educational institution. Thus, the publications in the «Odessa Herald» are an auxiliary source on the history of the Odessa Institute of Noble Maiden. They complement the existing archives and those related to the functioning of the educational institution.